An Empirical Formula for Assessing the Characteristic Strength of Unreinforced Laterite Stone Masonry - Hassane Seini Moussa; Decroly Djoubissié Denouwé; Abdou Lawane; Anne Pantet; Mamadou Diop; Koami Wisdom Boko (Salehan Institute of Higher Education, 2024)
This study aims to determine the needed coefficients for evaluating the uniaxial compressive strength characteristic value for masonry structures made of Laterite Stone (LS) and cement mortar, resulting from experiments conducted in the laboratory evaluating the compressive strengths of the laterite stone and mortar separately in masonry. It proposes calculation coefficients for the completion of Eurocode 6 data that fit the behavior of laterite stone-based masonry. The laterite stone blocks are extracted from three quarries in southern Burkina Faso. The dimensions of the masonry samples tested are 800 mm × 800 mm × 135 mm (±5 mm) with a cement mortar joint of 20 mm (±5 mm) thick. The different failure modes of masonry were also explored. The tests carried out on the masonry showed that the failure is initiated by vertical cracks through the block-mortar interface at a quarter of the width of the walls, generally at 40 to 60% of their maximum strength. The statistical analysis made through a linear regression from the standard model of approximation of the characteristic strength of masonry in Eurocode 6 was used to set out parameters for the empirical relation. The proposed formula considers the intrinsic properties of the block and the mortar, the thickness of the mortar, the dimensions of the masonry block, and the geometry of the masonry itself to evaluate its compression strength. The adequacy between the model and the experimental values is evaluated through the coefficient of determination and the standard error of 0.94 and 0.041 MPa, respectively. Doi: 10.28991/CEJ-2024-010-04-07 Full Text: PDF